Studies of natural gas production prediction and risk assessment for tight gas in Sichuan Basin - Li, Haitao; Yu, Guo; Fang, Yizhu; Chen, Yu; Zhang, Dongming (Frontiers in Earth Science, 2023)
The tight gas exploration and development potential in the Sichuan Basin is huge. Production prediction and risk quantification are important in planning of natural gas resources. The Ward model is used to predict the peak production of tight gas. Based on the prediction results, Hubbert and Gauss models are used to predict the production growth trend of the gas reservoir, and the Monte Carlo simulation is used to calculate the probability of production realization. The evaluation matrix of risk level is established by using indices of production realization probability and dispersion degree for assessing the risk level of tight gas production. The results show that: (1) compared to the Gauss model, the production prediction results of the Hubbert model have higher accuracy. The tight gas will reach peak production of (86-106)×10^8 m^3/a in 2042 and will have stable production from 2038 to 2046. By the end of the stable production stage, the URR exploitation degree is about 60%; and (2) The Monte Carlo method can be used to obtain the production realization probability for each year. The risk level evaluation matrix can be established by taking the probability of realization and the dispersion degree as evaluation indices, which can provide the systematization of the risk levels. The study can help to better understand the guiding significance for the natural gas exploration and development.